Alterations to dam‐spill discharge influence sex‐specific activity, behaviour and passage success of migrating adult sockeye salmon. Issue 4 (11th November 2013) - Burnett, Nicholas J.; Hinch, Scott G.; Donaldson, Michael R.; Furey, Nathan B.; Patterson, David A.; Roscoe, David W.; Cooke, Steven J.
ABSTRACT Delays in the freshwater spawning migrations of anadromous fishes at upstream barriers are well documented, but underlying mechanisms causing slowed migrations are seldom known. Using acoustic accelerometer transmitters and generalized linear models, we investigated how alterations in flow at a diversion dam in British Columbia, Canada, affected the activity, behaviour and passage success of a Fraser River sockeye salmon population (Oncorhynchus nerka). Spilling excess water through the radial gate of the dam decreased the attraction efficiency of a vertical‐slot fishway by 90% and increased delay below the dam by 2 h, which had adverse effects on passage. Relative to males, female sockeye salmon had significantly lower passage success (73% vs 94%), attraction efficiency (79% vs 100%) and passage efficiency (89% vs 94%) at a fishway, delayed longer in the dam tailrace (mean ± standard error (SE): 20·8 ± 4·1 h vs 14·6 ± 3·2 h), and resorted to anaerobic swimming efforts for a greater percentage of time (0–61·3% vs 0·7–2·7%). Given that the persistence of Pacific salmon populations relies on the spawning success of females, understanding how males and females vary in their response to modified flow regimes will improve the management of complex fish‐passage problems. Copyright © 2013 John Wiley & Sons, Ltd.